The constitutionality of electoral quotas for women - Diaz de Valdes, J; Jose Diaz de Valdes (2015)
This thesis explores the constitutionality of compulsory electoral quotas for women imposed by law. The central question this thesis attempts to answer is what makes these quotas constitutional or unconstitutional in a given jurisdiction. A double methodology was employed to answer this question: theoretical and comparative. From a theoretical perspective, it is proposed that the constitutionality of electoral quotas for women depends on the approach that domestic legal orders adopt to four issues: political representation, equality, affirmative action and political rights. An additional crosscutting factor that influences the constitutionality of these quotas is gender, mainly through its effects on the understanding of political representation and equality. From the comparative law perspective, three jurisdictions were analysed: France, Spain and Mexico. After exploring these systems' approaches to political representation, equality, affirmative action and political rights, the process of adoption of electoral quotas for women is discussed, particularly the constitutional litigation about quota laws. Finally, the relationship between the theory and the practice of assessing the constitutionality of electoral quotas for women is analysed, concluding that although courts use a theoretical framework formed by political representation, equality, affirmative action and political rights, they adopt a somewhat simplistic approach to these issues, using only one of these theoretical factors as the primary determinant, often side-stepping the most controversial issues connected with these factors, and almost completly ignoring the particularities of the target group (women). Additionally, in each jurisdiction the decisions of the courts are also influenced by domestic political and legal factors.